2021
DOI: 10.1002/pon.5746
|View full text |Cite
|
Sign up to set email alerts
|

Understanding context: A qualitative analysis of the roles of family caregivers of people living with cancer in Vietnam and the implications for service development in low‐income settings

Abstract: Objectives: Research on the needs of family caregivers of people living with cancer remains disproportionately focused in high income contexts. This research gap adds to the critical challenge on global equitable delivery of cancer care. This study describes the roles of family caregivers of people living with cancer in Vietnam and possible implications for intervention development. Methods: Semi-structured interviews and focus groups with family caregivers (n = 20) and health care providers (n = 22) were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…As well as identifying unique needs, such as advocating for cultural requirements, this study also corroborated the areas of support that have been previously reported for carers of non-Indigenous cancer survivors. This study's findings, such as the understanding the cultural needs of the cancer patient, align with the identified needs of family carers for cancer patients living in other countries [28]. Further, as found with other studies of carers of cancer survivors, carer needs relate to both providing care for the cancer survivor as well as the carer's own personal health and wellbeing.…”
Section: Discussionsupporting
confidence: 81%
“…As well as identifying unique needs, such as advocating for cultural requirements, this study also corroborated the areas of support that have been previously reported for carers of non-Indigenous cancer survivors. This study's findings, such as the understanding the cultural needs of the cancer patient, align with the identified needs of family carers for cancer patients living in other countries [28]. Further, as found with other studies of carers of cancer survivors, carer needs relate to both providing care for the cancer survivor as well as the carer's own personal health and wellbeing.…”
Section: Discussionsupporting
confidence: 81%
“…Informal caregivers are of particular importance to the delivery of care for Vietnamese NCDs patients. First, caregivers undertake multiple caring roles for patients, helping access health care, making treatment decisions, providing informational and emotional support, and basic care needs (ie, daily care, nutrition) [ 2 , 5 ]. Second, due to the inter-dependence of patient and caregivers’ health, supporting caregivers has the potential to impact upon patients’ health and well-being.…”
Section: Reflectionsmentioning
confidence: 99%
“…Prior to the outbreak, the burden of cancer on informal caregivers was already demonstrated to be significant [ 2 ]. In the context of COVID-19, this burden will increase.…”
Section: Reflectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies provided necessary information on the prevalence of diabetes, self-care practices and adherence to medicines [ 12 , 31 ] however, they do not help us to understand more about the patients and their caregivers’ perspectives on diabetes. A dyadic approach is required to understand patient and their caregiver perspectives on a disease because this is critical in shaping self-care practices especially for chronic conditions [ 32 , 33 ] including diabetes that requires long-term medical attention and care. The caregiver of a person suffering from NCDs undertakes multiple caring roles ranging from helping patients to access basic health care needs and making treatment decisions, to providing emotional and psychological support that have a bearing on a patient’s quality of life and wellbeing in general.…”
Section: Introductionmentioning
confidence: 99%